Factors Affecting Procedural Pain and Discomfort Experienced by Individuals During Nasopharyngeal Swabbing: A Cross-Sectional Study - Uğur Doğan; Gülsen Karataş; Sümeyra Mihrap İlter (AVES, 2024)
Aim: This descriptive and cross-sectional study investigated the individual factors that affect procedural pain and discomfort in individuals who had nasopharyngeal swabs by nurses. Methods: A total of 193 participants in two COVID-19 test centers located in a city in Southeastern Türkiye between April and May 2022 were included in this study. Personal information form was used to collect data. The visual analog scale was used to assess the pain and discomfort. Risk factors related to pain and discomfort were investigated through a logistic regression model. Results: During the nasopharyngeal swabbing, it was determined that pain was stronger in women and those who considered nasopharyngeal swabbing as a painful procedure (p < .05). Also, discomfort was stronger in women and those who considered nasopharyngeal swabbing as an uncomfortable procedure (p < .05). It was determined that the participants' discomfort scores were higher than their pain scores. Conclusion: Women and individuals with negative opinions about the procedure experienced more pain and discomfort during the nasopharyngeal swabbing. Most of the participants complained more about discomfort than pain. It is recommended to apply alternate test methods and conduct nurse-led information studies to reduce the anticipation of procedural pain/discomfort.